1998
DOI: 10.1080/02652039809374629
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in ingredients of animal feeding stuffs: III. determination of mycotoxins in rice bran

Abstract: Methods used previously for the determination of aflatoxins B1, B2, G1 and G2, ochratoxins A and B, cyclopiazonic acid, zearalenone, sterigmatocystin, and moniliformin in maize were applied successfully to rice bran. However, recovery of deoxynivalenol and other trichothecene mycotoxins spiked into samples was lower than expected and no citrinin could be recovered. Forty samples of rice bran used in the animal feed industry were examined for the presence of 20 mycotoxins. The level of contamination of rice bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…By this method, the detection limit for citrinin was achieved to 10 ng/g. In succession, liquid chromatography using reversed-phase columns and fluorescence detection was successfully used to quantify citrinin in grains (Dick, Baumann, & Zimmerli, 1988;Lepom, 1986;Scudamore, Nawaz, Hetmanski, & Rainbird, 1998;Zimmerli et al, 1989), feeds (Schneweis et al, 2001;Scudamore & Hetmanski, 1992;Scudamore et al, 1997), cheese Vazquez et al, 1996), and fungal cultures Vail & Homann, 1990). Selective separations were generally optimized by using ternary or even quaternary eluent systems.…”
Section: Hplc-uv Techniquementioning
confidence: 99%
“…By this method, the detection limit for citrinin was achieved to 10 ng/g. In succession, liquid chromatography using reversed-phase columns and fluorescence detection was successfully used to quantify citrinin in grains (Dick, Baumann, & Zimmerli, 1988;Lepom, 1986;Scudamore, Nawaz, Hetmanski, & Rainbird, 1998;Zimmerli et al, 1989), feeds (Schneweis et al, 2001;Scudamore & Hetmanski, 1992;Scudamore et al, 1997), cheese Vazquez et al, 1996), and fungal cultures Vail & Homann, 1990). Selective separations were generally optimized by using ternary or even quaternary eluent systems.…”
Section: Hplc-uv Techniquementioning
confidence: 99%
“…Aflatoxins may occur in peanuts, corn (maize) and cottonseed, as well as in many other agricultural commodities ( Pittet 2001 ). Occurrence in rice has also been reported in a number of countries ( Reddy et al 2008 ; Gummert et al 2009 ): Sri Lanka ( Bandara et al 1991 ), Bangladesh ( Dawlatana et al 2002 ), Japan ( Tabata et al 1993 ), China ( Liu and Gao 2006 ; Wang and Liu 2007 ), Vietnam ( Nguyen et al 2007 ), Thailand ( Shank et al 1972 ), India ( Pande et al 1990 ; Toteja et al 2006 ; Reddy et al 2009 ), the Philippines ( Sales and Yoshizawa 2005 ), Korea ( Park et al 2004 , 2005a ), United Arab Emirates ( Osman et al 1999 ), Turkey ( Aydin et al 2010 ), Tunisia ( Ghali et al 2008 ), Nigeria ( Hussaini et al 2007 ), Côte d'Ivoire ( Sangare-Tigori et al 2006b ), Uruguay ( Piñeiro et al 1996 ), Brazil ( Soares and Rodriguez-Amaya 1989 ; de Carvalho et al 2010 ), and the United States ( Abbas and Shier 2009 ), as well as in imported/ marketed rice in the United Kingdom ( Scudamore et al 1998 ; Food Standards Agency (FSA) 2002 ), Austria ( Reiter et al 2010 ), Iran ( Mazaheri 2009 ) and Sweden ( Fredlund et al 2009 ; Nordkvist et al 2009 ). The study in Vietnam indicated that the rainy season was a major risk factor for occurrence of AFB 1 in rice ( Nguyen et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traces of ochratoxin A have been detected in fermentation products such as beer ( Scott & Kanhere, 1995; Scott, 1996) as well as in coffee ( Patel et al ., 1997 ; Stegen et al ., 1997 ). Ochratoxin A occurs in animal‐derived food products ( Hohler, 1998) such as pork and poultry meat ( Jorgensen, 1998) by so‐called carry‐over as a result of feeding the animals contaminated fodder ( Abramson et al ., 1997 ; Scudamore et al ., 1997 , 1998a, 1998b). OTA concentrations as high as 8 μg/kg have also been found in both liver and blood sausage as well as in the offal of pigs ( Scheuer, 1989; Scheuer et al ., 1997 ).…”
Section: Introductionmentioning
confidence: 99%